(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article explores practical strategies for implementing the flipped classroom model to teach B2-level writing in Uzbekistan, aligning with CEFR standards. It details pre-class activities, such as instructional videos and genre exemplars, and in-class collaborative tasks, peer reviews, and revision workshops, supported by digital tools like Google Docs, Padlet, and AI-based platforms. The approach fosters learner autonomy, metalinguistic awareness, and process-based writing skills. Despite challenges in Uzbekistan, including limited technology access and unfamiliarity with autonomous learning, localized adaptations like mobile-friendly materials and culturally relevant exemplars enhance effectiveness. The study highlights how strategic implementation improves linguistic competence and empowers students as independent, reflective academic writers.